Implementasi Logika Fuzzy untuk Purwarupa Pengkondisian AC dan Lampu Otomatis pada Sebuah Ruangan - Nana Amalia Mulia; Mochammad Hannats Hanafi; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
As the year increase, the demand for electricity increase. Every building either mansion or house mostly has electronic equipment, such as light. Besides, AC is quite expensive of electronic equipment which the electrical power required is quite large. Electronic equipment certainly requires electrical energy. However, it usually only uses the on-off principle. It is certainly can reduce the lifetime of equipments, waste the electrical energy, and cause the room temperature condition become uncontrollable. In this study made conditioning system of automatic AC and light using Fuzzy Sugeno logic. The system using input of light from LDR sensor, temperature and humidity from DHT11 sensor, and movement from PIR HC-SR501 sensor. Next, using Arduino Uno microcontroller to process and the result is numeric which displayed on LCD. Design of Fuzzy logic consist of fuzzification, which is forming Fuzzy set of input variables, inference is the step to forming set of rules, and defuzzification is the step to determine the results. Implementation of Fuzzy logic consist of made program code to calculate the membership degree from input variables of light, temperature, and humidity, next, program code to find Î±-predicate value of each rules, and the last, program code to find z value which done twice, for AC and light condition. The success rate of Fuzzy logic is done by comparing the output value of system with MATLAB. The accuracy average of AC output is 97.21%, while the light is 93.75%.